2018
DOI: 10.1111/ipd.12441
|View full text |Cite
|
Sign up to set email alerts
|

Does oral health influence school performance and school attendance? A systematic review and meta‐analysis

Abstract: Aim To examine the evidence on the influence of oral health status on school performance and school attendance in children and adolescents. Design A systematic review was performed in accordance with PRISMA included epidemiological studies that assessed concomitantly oral health measures, participants’ school performance and/or school attendance. Electronic search was conducted on MEDLINE, SCOPUS, Web of Science, ScienceDirect, and LILACS. Studies published up to May 2018 in any language were eligible. The ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 36 publications
(167 reference statements)
3
88
1
10
Order By: Relevance
“…This could explain how oral diseases (particularly dental caries) have an impact on OHRQoL, which again negatively influence school performance. Association between untreated dental caries and high school absenteeism consequently resulting in poor school performance is in concordance with recent systematic reviews, which most likely is the case here as well . Kaewkamnerdpong and Krisdapong also reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could explain how oral diseases (particularly dental caries) have an impact on OHRQoL, which again negatively influence school performance. Association between untreated dental caries and high school absenteeism consequently resulting in poor school performance is in concordance with recent systematic reviews, which most likely is the case here as well . Kaewkamnerdpong and Krisdapong also reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, these oral problems also affect the schoolwork and learning process, as children are likely to miss school due to oral pain or infection, which are often consequences of untreated dental caries in children . This was evident in recent systematic reviews, which concluded that children with a high dental caries rate have poor school attendance and poor academic achievement . In a longitudinal study, when treatments for decayed teeth were provided, significant improvement on OHRQoL was demonstrated among South Brazilian adolescents …”
Section: Introductionmentioning
confidence: 99%
“…Hay evidencia sobre la correlación entre el índice de higiene oral y la calidad de vida relacionada a la salud bucal (26) . Adicionalmente, una revisión sistemática establece que los niños con uno o más dientes con lesiones de caries genera consecuencias negativas en el desempeño y asistencia escolar cuando se comparan con niños con dentición saludable (27) ; tendencias de AFC en países desarrollados muestran mejor adherencia educativa (28) . En la mayoría de las investigaciones, al igual que en el presente estudio, las frecuencias de cepillado incrementan con la edad.…”
Section: Discussionunclassified
“…In the dental context, there is some evidence that dental caries, toothache, gingivitis and dentofacial features are oral disorders that compromise academic activities, increasing absenteeism and decreasing the school performance of children and adolescents 13 - 15 . However, nothing is known about the impact of oral changes on school failure.…”
Section: Introductionmentioning
confidence: 99%